MAKNA SIMBOL VISUAL PIYAMA DALAM FILM "THE BOY WITH THE STRIPPED PAJAMAS" - Prasanti, Ditha; Indriani, Sri Seti (ATRAT: Jurnal Seni Rupa, 2016)
Film is an audiovisual tool that departs from visual mass communication. Movies can also influence attitudes, behavior, and expectations of the people who watch it in all over the world. 'The boy with the striped pajamas' is a sad film that tells how pride oneself on one’s own race could be a deadly boomerang. The film recalls what happened to the Jews in the second world war in Germany under the rule of 'the Führer' Adolf Hitler. This study intends to look at the meaning of pajamas as visual symbols in the film relating to racism. The study used qualitative approach and semiotic analysis method of Roland Barthes. The semiotic method is employed to analyze the phenomenon in terms of signs and meanings. The results of this study indicate that the meaning of signs and markers in the movie The Boy with the Stripped Pajamas can be studied from the meaning of denotation, connotation, and myth. Denotation meaning of Pajamas as visual symbols in the film is the emphasized clothes symbol because they are always worn by the child. Connotation meaning of pajamas as visual symbols in this film is not limited to clothes, but rather a symbol of racism arising from the difference between the two tribes. Myth meaning of pajamas as visual symbols in this film is being barred in a prison, the child who wears this is considered a criminal who has no freedom and must be punished.Keywords: Meanings, symbols, Pajamas, Semiotics, Film________________________________________________________________ Film merupakan sebuah alat audiovisual yang bergerak dari komunikasi massa visual. Film juga dapat  mempengaruhi sikap, perilaku, dan harapan orang-orang yang menontonnya di belahan dunia. Film ‘The boy with the stripped pajamas’ adalah film yang sangat memilukan, diceritakan bagaimana ‘kebanggaan’ terhadap ras sendiri bisa menjadi bumerang tajam yang mematikan. Film ini mengangkat kembali apa yang terjadi dengan kaum yahudi pada perang dunia kedua di Jerman di bawah kekuasaan ‘the Furrer’ Adoilf Hitler. Penelitian ini bermaksud untuk melihat makna simbol visual Piyama dari film tersebut yang berkaitan dengan rasisme. Pendekatan penelitian yang digunakan dalam penelitian ini adalah pendekatan kualitatif dengan metode semiotika analisis Roland Barthes. Metode semiotika ini menganalisis fenomena dari segi tanda dan makna. Hasil penelitian ini menunjukkan bahwa  makna tanda dan penanda dalam film The Boy with the Stripped Pajamas dapat dikaji dari makna denotasi, makna konotasi, dan makna mitos. Makna denotasi dari simbol visual Piyama dalam film ini adalah simbol pakaian yang selalu ditonjolkan karena digunakan oleh anak tersebut. Makna konotasi dari simbol visual Piyama dalam film ini adalah tidak sebatas pakaian, melainkan sebuah simbol rasisme yang dimunculkan dari perbedaan kedua suku yang ada. Makna mitos dari simbol visual Piyama dalam film ini adalah terkurung dalam penjara, anak yang memakainya dianggap penjahat, tidak memiliki kebebasan, dan harus dihukum.Kata Kunci: Makna, Simbol, Piyama, Semiotika, Film